z^4+i=0 equation
The teacher will be very surprised to see your correct solution 😉
The solution
Detail solution
Given the equation
z 4 + i = 0 z^{4} + i = 0 z 4 + i = 0 Because equation degree is equal to = 4 and the free term = -i complex,
so the real solutions of the equation d'not exist
All other 4 root(s) is the complex numbers.
do replacement:
w = z w = z w = z then the equation will be the:
w 4 = − i w^{4} = - i w 4 = − i Any complex number can presented so:
w = r e i p w = r e^{i p} w = r e i p substitute to the equation
r 4 e 4 i p = − i r^{4} e^{4 i p} = - i r 4 e 4 i p = − i where
r = 1 r = 1 r = 1 - the magnitude of the complex number
Substitute r:
e 4 i p = − i e^{4 i p} = - i e 4 i p = − i Using Euler’s formula, we find roots for p
i sin ( 4 p ) + cos ( 4 p ) = − i i \sin{\left(4 p \right)} + \cos{\left(4 p \right)} = - i i sin ( 4 p ) + cos ( 4 p ) = − i so
cos ( 4 p ) = 0 \cos{\left(4 p \right)} = 0 cos ( 4 p ) = 0 and
sin ( 4 p ) = − 1 \sin{\left(4 p \right)} = -1 sin ( 4 p ) = − 1 then
p = π N 2 − π 8 p = \frac{\pi N}{2} - \frac{\pi}{8} p = 2 π N − 8 π where N=0,1,2,3,...
Looping through the values of N and substituting p into the formula for w
Consequently, the solution will be for w:
w 1 = − 1 2 − 2 4 − i 2 4 + 1 2 w_{1} = - \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} - i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} w 1 = − 2 1 − 4 2 − i 4 2 + 2 1 w 2 = 1 2 − 2 4 + i 2 4 + 1 2 w_{2} = \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} + i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} w 2 = 2 1 − 4 2 + i 4 2 + 2 1 w 3 = − 2 4 + 1 2 + i 1 2 − 2 4 w_{3} = - \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} + i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} w 3 = − 4 2 + 2 1 + i 2 1 − 4 2 w 4 = 2 4 + 1 2 − i 1 2 − 2 4 w_{4} = \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} - i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} w 4 = 4 2 + 2 1 − i 2 1 − 4 2 do backward replacement
w = z w = z w = z z = w z = w z = w The final answer:
z 1 = − 1 2 − 2 4 − i 2 4 + 1 2 z_{1} = - \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} - i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} z 1 = − 2 1 − 4 2 − i 4 2 + 2 1 z 2 = 1 2 − 2 4 + i 2 4 + 1 2 z_{2} = \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} + i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} z 2 = 2 1 − 4 2 + i 4 2 + 2 1 z 3 = − 2 4 + 1 2 + i 1 2 − 2 4 z_{3} = - \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} + i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} z 3 = − 4 2 + 2 1 + i 2 1 − 4 2 z 4 = 2 4 + 1 2 − i 1 2 − 2 4 z_{4} = \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} - i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} z 4 = 4 2 + 2 1 − i 2 1 − 4 2
___________ ___________
/ ___ / ___
/ 1 \/ 2 / 1 \/ 2
z1 = - / - - ----- - I* / - + -----
\/ 2 4 \/ 2 4
z 1 = − 1 2 − 2 4 − i 2 4 + 1 2 z_{1} = - \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} - i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} z 1 = − 2 1 − 4 2 − i 4 2 + 2 1
___________ ___________
/ ___ / ___
/ 1 \/ 2 / 1 \/ 2
z2 = / - - ----- + I* / - + -----
\/ 2 4 \/ 2 4
z 2 = 1 2 − 2 4 + i 2 4 + 1 2 z_{2} = \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} + i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} z 2 = 2 1 − 4 2 + i 4 2 + 2 1
___________ ___________
/ ___ / ___
/ 1 \/ 2 / 1 \/ 2
z3 = - / - + ----- + I* / - - -----
\/ 2 4 \/ 2 4
z 3 = − 2 4 + 1 2 + i 1 2 − 2 4 z_{3} = - \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} + i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} z 3 = − 4 2 + 2 1 + i 2 1 − 4 2
___________ ___________
/ ___ / ___
/ 1 \/ 2 / 1 \/ 2
z4 = / - + ----- - I* / - - -----
\/ 2 4 \/ 2 4
z 4 = 2 4 + 1 2 − i 1 2 − 2 4 z_{4} = \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} - i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} z 4 = 4 2 + 2 1 − i 2 1 − 4 2
z4 = sqrt(sqrt(2)/4 + 1/2) - i*sqrt(1/2 - sqrt(2)/4)
Sum and product of roots
[src]
___________ ___________ ___________ ___________ ___________ ___________ ___________ ___________
/ ___ / ___ / ___ / ___ / ___ / ___ / ___ / ___
/ 1 \/ 2 / 1 \/ 2 / 1 \/ 2 / 1 \/ 2 / 1 \/ 2 / 1 \/ 2 / 1 \/ 2 / 1 \/ 2
- / - - ----- - I* / - + ----- + / - - ----- + I* / - + ----- + - / - + ----- + I* / - - ----- + / - + ----- - I* / - - -----
\/ 2 4 \/ 2 4 \/ 2 4 \/ 2 4 \/ 2 4 \/ 2 4 \/ 2 4 \/ 2 4
( 2 4 + 1 2 − i 1 2 − 2 4 ) + ( ( ( − 1 2 − 2 4 − i 2 4 + 1 2 ) + ( 1 2 − 2 4 + i 2 4 + 1 2 ) ) + ( − 2 4 + 1 2 + i 1 2 − 2 4 ) ) \left(\sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} - i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}}\right) + \left(\left(\left(- \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} - i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}}\right) + \left(\sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} + i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}}\right)\right) + \left(- \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} + i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}}\right)\right) 4 2 + 2 1 − i 2 1 − 4 2 + − 2 1 − 4 2 − i 4 2 + 2 1 + 2 1 − 4 2 + i 4 2 + 2 1 + − 4 2 + 2 1 + i 2 1 − 4 2
/ ___________ ___________\ / ___________ ___________\ / ___________ ___________\ / ___________ ___________\
| / ___ / ___ | | / ___ / ___ | | / ___ / ___ | | / ___ / ___ |
| / 1 \/ 2 / 1 \/ 2 | | / 1 \/ 2 / 1 \/ 2 | | / 1 \/ 2 / 1 \/ 2 | | / 1 \/ 2 / 1 \/ 2 |
|- / - - ----- - I* / - + ----- |*| / - - ----- + I* / - + ----- |*|- / - + ----- + I* / - - ----- |*| / - + ----- - I* / - - ----- |
\ \/ 2 4 \/ 2 4 / \\/ 2 4 \/ 2 4 / \ \/ 2 4 \/ 2 4 / \\/ 2 4 \/ 2 4 /
( − 1 2 − 2 4 − i 2 4 + 1 2 ) ( 1 2 − 2 4 + i 2 4 + 1 2 ) ( − 2 4 + 1 2 + i 1 2 − 2 4 ) ( 2 4 + 1 2 − i 1 2 − 2 4 ) \left(- \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} - i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}}\right) \left(\sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}} + i \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}}\right) \left(- \sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} + i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}}\right) \left(\sqrt{\frac{\sqrt{2}}{4} + \frac{1}{2}} - i \sqrt{\frac{1}{2} - \frac{\sqrt{2}}{4}}\right) − 2 1 − 4 2 − i 4 2 + 2 1 2 1 − 4 2 + i 4 2 + 2 1 − 4 2 + 2 1 + i 2 1 − 4 2 4 2 + 2 1 − i 2 1 − 4 2
z1 = 0.38268343236509 + 0.923879532511287*i
z2 = -0.923879532511287 + 0.38268343236509*i
z3 = -0.38268343236509 - 0.923879532511287*i
z4 = 0.923879532511287 - 0.38268343236509*i
z4 = 0.923879532511287 - 0.38268343236509*i